Effect of Binocular Vision Problems on Childhood Academic Performance and Teachers’ Perspective: Doi: 10.36351/pjo.v36i2.896 - Alrasheed, Saif Hassan; Elmadina, Abd Elaziz Mohamed (Pakistan Journal of Ophthalmology, 2020)
Purpose: To see the effect of binocular vision problems on childhood academic performance and to record the teacher’s perspectives about childhood eye care in Khartoum State of Sudan. Place and Duration of Study: A descriptive cross-sectional study done among the school going children in the Khartoum State of Sudan during the year 2018. Study Design: Descriptive cross sectional study. Material and Methods: Three hundred and forty (340) primary school children’s were recruited for study by convenient sampling technique during the academic year 2018. After relevant history, ocular examination was performed. It included visual acuity measurement, assessment of refractive errors and binocular function tests. Academic performance of the children was recorded from academic records of the children. Finally, the qualitative data was derived from teachers’ perspectives about childhood eye care. Results: Mean age of the participants was 11.96 ± 1.63 years. The findings revealed that (78.6%) of children achieved poor academic performances with decompensated exophoria at near. 52.7% children with poor academic performances had weak positive fusion reserve at near P = 0.04. 37.2% of the poor performers had convergence insufficiency. Fort eight percent of females with ocular complaints achieved poor academic performances P = 0.034. With regard to teacher’s perspectives about childhood eye care, 98.8%believed that the vision problems had effect on the academic record of the children. Seventy percent of the teachers reported that the students did not undergo eye examinations before joining school. Conclusion: Convergence Insufficiency and weak positive fusional reserve at near has a significant effect on academic performances.